On the numerical solution of the system of two-dimensional Burgers' equations by the decomposition method - El-Sayed, SM; Kaya, D (Elsevier Science Inc, 2004)
Adomian's decomposition method (ADM) is proposed to approximate the numerical and analytical solutions of system two-dimensional Burgers' equations (STDBE) with initial conditions. The advantages of this work are the decomposition method reduces the computational work and improvement with regard to its accuracy and rapid convergence. Some examples are given to illustrate the performance of the method described. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: two-dimensional Burgers' equations; Adomian's decomposition method; Adomian's polynomials